The effect of added banana flower on acceptance and chemical properties shredded bamboo shoots - Runia Sativa; Andriani Andriani; Erwandi Erwandi; Wiqayatun Khazanah (JAND: Journal of Applied Nutrition and Dietetic, 2021)
One of the foods that are high in fiber other than bamboo (bamboo shoots) is banana flower with a high fiber content which will benefit the elderly by processing it into shreds, as a substitute for crude fiber and also has many benefits for body health. This research is experimental with three treatments and three repetitions with the addition of 20 grams, 30 grams and 40 grams of banana heart. The panelists used in this study were semi-panelists. The research methods: This type of research is experimental with a Completely Randomized Design (CRD), specifically 3 treatments and 3 repetitions using the hedonic test. Up to 30 people were trained from students at the Department of Nutrition, Ministry of Health, Aceh. Utilizing ANOVA (Analysis Of Variance) and Duncan's Multiple Test Further Test, data processing and analysis were performed. The addition of 20 g, 30 g and 40 g of banana flower had no significant effect on the color of the shredded bamboo shoots. The addition of 20 g, 30 g and 40 g of banana flower had a significant effect on the taste, aroma and texture of shredded bamboo shoots. The high water content in shredded bamboo shoots is influenced by the process of boiling ingredients such as bamboo shoots and banana buds, to reduce the water content it can be seen through the frying process which then shrinks.